2008
DOI: 10.4049/jimmunol.180.6.3874
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Epithelial Cell Up-Regulation of LY6 Molecules during Colitis Results in Enhanced Chemokine Secretion

Abstract: In the healthy colon, intestinal epithelial cells (IEC) form a physical barrier separating the myriad of gut Ags from the cells of the immune system. Simultaneously, IEC use several mechanisms to actively maintain immunologic tolerance to nonpathogenic Ags, including commensal bacteria. However, during inflammatory bowel disease (IBD), the line of defense provided by IEC is breached, resulting in uncontrolled immune responses. As IEC are a principal mediator of immune responses in the gut, we were interested i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 57 publications
(47 reference statements)
2
30
0
Order By: Relevance
“…2A). In addition, infiltration of CD11c + cells together with proinflammatory Ly-6C hi monocytes were a sign of pronounced colonic inflammation, as previously observed in patients with IBD (17). Differences in leukocyte infiltration between Il10 −/− (33%) and S3/I10 −/− mice (22%) persisted at 14 wk of age ( Fig.…”
Section: Significancesupporting
confidence: 61%
“…2A). In addition, infiltration of CD11c + cells together with proinflammatory Ly-6C hi monocytes were a sign of pronounced colonic inflammation, as previously observed in patients with IBD (17). Differences in leukocyte infiltration between Il10 −/− (33%) and S3/I10 −/− mice (22%) persisted at 14 wk of age ( Fig.…”
Section: Significancesupporting
confidence: 61%
“…The simplest explanation is that IFN-␥ activates macrophages and neutrophils for E. histolytica killing, which has been shown in vitro (13,36). Alternately, it is possible that IFN-␥ exerts protective effects (e.g., inducing production of chemokines [15,18] and mucosal defense molecules [16]) on the epithelium, which bone marrow chimera experiments indicate is a critical cell type in the mouse strain-specific resistance to intestinal E. histolytica infection (23).…”
Section: Discussionmentioning
confidence: 99%
“…Those authors identified the LY6A gene superfamily as strongly upregulated in inflamed intestinal epithelial cells. The majority of LY6 family members are GPI-anchored cell surface glycoproteins with broad distribution on cells of hematopoietic origin (32). Surface expression of LY6A was induced by IL-22 and interferon (IFN)-␥ and resulted in production of a number of chemokines known to be involved in the immunopathogenesis of IBD.…”
Section: Epithelial Barriermentioning
confidence: 99%